Water, sanitation and hygiene (WASH) for the prevention and care of NTDs - Velleman, Yael (Henry Stewart Talks, 2019)
An outline of WASH, How access to WASH is estimated, The association between poor sanitation/water access and NTDs, ‘Ladders’ for schools and healthcare facilities, Global situation masks inequalities, The intimate link between WASH and NTDs, The challenge presented by the required multisectoral action, The global response to the challenge, Key lessons that have been learned